Pressure transducers for cryogenic liquids - Pavlovskyy I. V.; Kutrakov A. P.; Maryamova I. I.; Druzhinin A. A. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2007)
The developed universal construction of tensoresistive pressure transducer for cryogenic liquids (liquid nitrogen and liquid helium) is described. The study of strain gauges characteristics on the basis of p-type Si whiskers with different boron concentration, mounted on the invar spring elements (beams), in the wide ranges of strain ε=±1,2·10-3 and temperature 4,2-300 К for transducers simulation were carried out. It was shown that using heavily doped silicon strain gages gives the possibility to develop pressure transducers for liquid nitrogen and liquid helium based on the classic piezoresistance. The significant increasing of the pressure transducers sensitivity for liquid helium could be achieved by using the strain gages on the basis of silicon with boron concentration in the vicinity of metal-insulator transition based on the non-classic piezoresitance. Developed pressure transducers for cryogenic liquids with strain gauges on the basis of doped p-type Si whiskers are presented.